Targeting the ERK1/2 and p38 MAPK pathways attenuates Golgi tethering factor golgin-97 depletion-induced cancer progression in breast cancer - Yu-Chin Liu; Tsung-Jen Lin; Kowit-Yu Chong; Guan-Ying Chen; Chia-Yu Kuo; Yi-Yun Lin; Chia-Wei Chang; Ting-Feng Hsiao; Chih-Liang Wang; Yo-Chen Shih; Chia-Jung Yu (Cell Communication and Signaling)
Abstract Background The Golgi apparatus is widely considered a secretory center and a hub for different signaling pathways. Abnormalities in Golgi dynamics can perturb the tumor microenvironment and influence cell migration. Therefore, unraveling the regulatory network of the Golgi and searching for pharmacological targets would facilitate the development of novel anticancer therapies. Previously, we reported an unconventional role for the Golgi tethering factor golgin-97 in inhibiting breast cell motility, and its downregulation was associated with poor patient prognosis. However, the specific role and regulatory mechanism of golgin-97 in cancer progression in vivo remain unclear. Methods We integrated genetic knockout (KO) of golgin-97, animal models (zebrafish and xenograft mice), multi-omics analysis (next-generation sequencing and proteomics), bioinformatics analysis, and kinase inhibitor treatment to evaluate the effects of golgin-97 KO in triple-negative breast cancer cells. Gene knockdown and kinase inhibitor treatment followed by qRT‒PCR, Western blotting, cell viability, migration, and cytotoxicity assays were performed to elucidate the mechanisms of golgin-97 KO-mediated cancer invasion. A xenograft mouse model was used to investigate cancer progression and drug therapy. Results We demonstrated that golgin-97 KO promoted breast cell metastasis in zebrafish and xenograft mouse models. Multi-omics analysis revealed that the Wnt signaling pathway, MAPK kinase cascades, and inflammatory cytokines are involved in golgin-97 KO-induced breast cancer progression. Targeting the ERK1/2 and p38 MAPK pathways effectively attenuated golgin-97-induced cancer cell migration, reduced the expression of inflammatory mediators, and enhanced the chemotherapeutic effect of paclitaxel in vitro and in vivo. Specifically, compared with the paclitaxel regimen, the combination of ERK1/2 and p38 MAPK inhibitors significantly prevented lung metastasis and lung injury. We further demonstrated that hypoxia is a physiological condition that reduces golgin-97 expression in cancer, revealing a novel and potential feedback loop between ERK/MAPK signaling and golgin-97. Conclusion Our results collectively support a novel regulatory role of golgin-97 in ERK/MAPK signaling and the tumor microenvironment, possibly providing new insights for anti-breast cancer drug development.